Estructura poblacional y distribución espacial del roble negro (Colombobalanus excelsa, Fagaceae), especie endémica, en fragmentos de bosque andino colombiano - Aguirre-Acosta, Natalia (2018)
Population structure and spatial distribution of black oak (Colombobalanus excelsa, Fagaceae), endemic species, in Colombian Andean forest fragments. The Colombian Andean forests are recognized for its great biodiversity and endemism; however, they have undergone a severe process of fragmentation due to anthropic factors. As a result, many vulnerable species have been especially affected. That is the case of the black oak (Colombobalanus excelsa (Lozano, Hern. Cam., & Henao) Nixon & Crepet), an endemic and poorly studied species of the Colombian Andes, which has a distribution restricted to only four areas in the country, one of which is the Southeastern Huila region. To examine black oak populations in Serranía Peñas Blancas (Huila), in 2006 we studied the age structure and spatial distribution in plots of 50 x 20 m (1.6 ha) in forest fragments, in southern distribution. In total, 1 228 black oak species were registered among saplings, juvenile and adults, and they have distribution patterns Gamma and Weibull. These results confirm that the majority of the individuals are in the first diametric class. Also, these populations show an added distribution pattern due to the wood extraction process. These results indicate that black oak populations are in a recovery phase after forceful anthropic intervention. Knowing the current status of black oak forests can contribute to the design of effective conservation plans of this species in Colombia. Rev. Biol. Trop. 66(2): 486-494. Epub 2018 June 01.